Sugars in Antimicrobial Polymers – The Impact of Sugar‐Lectin Binding in Membrane Interaction of Cationic Glycopolymers - Alain M. Bapolisi; Steffen Tank; Anne‐Catherine Lehnen; Antje Stindt; Rujuta Athavale; Jan A. M. Kurki; Sany Chea; Sophia Rosencrantz; Ruben R. Rosencrantz; Katja M. Arndt; Matthias Hartlieb (Advanced Materials Interfaces)
Abstract Membrane‐active antimicrobial polymers (APs) are promising alternatives for treating infectious diseases as they are less susceptible to antimicrobial resistance development. However, their non‐specific cytotoxicity limits their clinical application. One interesting strategy to improve cytocompatibility is the incorporation of sugar units into APs. This approach takes advantage of specific interactions between sugars and protein receptors, such as lectins, on the surface of bacteria, potentially allowing for discrimination between different bacterial types. However, there is limited research on how sugar addition to cationic APs affects their selectivity and interactions with lectins. Herein, a library of acrylamide‐based cationic glycopolymers is synthesized by a xanthate‐supported photo‐initiated Reversible Additon‐Fragmentation chain Trasnfer (XPI‐RAFT) polymerization. Diverse sugars are added to this cationic scaffold by either chain extension with glycomonomers (based on fucose, glucose, mannose, and polyhydroxy acrylamide) or simply by reductive amination (lactose and melibiose). Various analytical techniques are used to probe the interaction of (glyco)polymers with bacteria, membrane models, and lectins. In general, (glyco)polyhydroxy incorporation proves to reduce the hydrophobicity of the cationic APs and consequently enhances hemocompatibility while maintaining the antimicrobial activity. Although sugar‐protein‐specific recognition may contribute to selectivity, the results demonstrate that electrostatic interaction predominantly drives the binding efficacy of cationic glycopolymers to bacterial membranes.